Shahab Ahmad’s Hostile-Intellectual Approach towards Ḥadīth Sciences - Awan, Muhammad Iqbal; Qadri, Hafiz Khurshid Ahmad (Journal of Islamic and Religious Studies, 2020)
The article strives to expose the attitude of a western grown Muslim scholar Shahab Ahmad (1966 – 2015 AD) to the 2nd major Islamic source Ḥadīth and its sciences. The question to be answered here is what kind of approach, hostile or supporting, Shahab had towards Ḥadīth sciences? Many critics knocked his corpus regarding his modern conceptualization of Islam, but his Ḥadīth sense remained undiscussed yet. This paper encircled all his Ḥadīth treatment while using the analytical research approach. Shahab seems facing a great opposition of Ḥadīth terminology in the way of proving his life-argument of ‘satanic verses’. Shahab put several grave accusations on Muḥaddithīn (the traditionists) just like as “adjusters” and “editors” of chains and “underminers of text”. His excessive usage of deficient and incomplete chains of transmission to prove his argument, his acceptance of omitted chains and declaration of complete chains as ‘fabricated’, his ‘self-assumptions’ in the chains all depict his ill-will. By going through his oeuvre, it becomes apparent that Shahab Ahmad criticized almost the entire process of Ḥadīth Sciences which shows his hostility and less knowledge of Ḥadīth. Being taught in secular institutions of the West, Shahab Ahmad had a hostile attitude towards Ḥadīth sciences.